An Atopic Dermatitis-Like Mouse Model by Alternate Epicutaneous Application of Dinitrofluorobenzene and an Extract of Dermatophagoides Farinae - Feng, Shujing; Liu, Wengying; Deng, Sisi; Song, Guoxuan; Zhou, Jie; Zheng, Zhengni; Song, Zhiqiang (Frontiers in Medicine, 2022)
Several studies have tried to establish mice models of atopic dermatitis (AD) through the allergen of Dermatophagoides farinae (Df). However, there are no typical skin lesions after epicutaneous application of an extract of Df (DfE) on BALB/c mice. Dinitrofluorobenzene (DNFB) is a common hapten that brings about contact dermatitis. Skin dysfunction induced by DNFB may be a way to enhance the effects of DfE on mice skin. Thus, we hypothesized that alternate epicutaneous application of DNFB and DfE could induce AD-like skin lesions on BALB/c mice. To test this hypothesis, we alternately applied the DNFB and DfE to the back skin of BALB/c mice for 8 weeks. Changes in mice skin lesions and the frequency of scratching behavior were recorded. The variation of Th1-related cytokines (interferon-γ [IFN-γ] and interleukin two [IL-2]) and Th2-related cytokines (IL-4 and IL-13) was detected in serum and lesional skin. Eventually, the BALB/c mice developed severe erythema, erosion, scarring, and excoriation on the entire back, showing a high frequency of scratching behavior. In addition, Th2 cells' dominant cytokines appeared in both serum and lesional skin. Those results indicate that alternating epicutaneous exposure to DNFB and DfE can produce AD-like models with typical clinical features and Th2-type immune responses in BALB/c mice. This model could be valuable for studying the pathogenesis of AD and developing novel therapeutic agents for it.